Pulsed Electrical Stimulation Enhances Consistency of Directional Migration of Adipose-Derived Stem Cells - Mi Hee Lee; Ye Jin Park; Seung Hee Hong; Min-Ah Koo; Minyoung Cho; Jong-Chul Park (Cells, 2021)
Electrical stimulation is a well-known strategy for regulating cell behavior, both in pathological and physiological processes such as wound healing, tissue regeneration, and embryonic development. Electrotaxis is the directional migration of cells toward the cathode or anode when subjected to electrical stimulation. In this study, we investigated the conditions for enhanced directional migration of electrically stimulated adipose-derived stem cells (ADSCs) during prolonged culture, using a customized agar-salt electrotaxis chamber. Exposure of ADSCs to a 1200 μA electric current for 3 h, followed by cessation of stimulation for 6 h and resumed stimulation for a further 3 h, increased directional cell migration toward the anode without inducing cell death. Moreover, Golgi polarization maintained the direction of polarity parallel to the direction of cell movement. Herein, we demonstrated that a pulsed electric current is sufficient to trigger directional migration of ADSCs in long-term culture while maintaining cell viability.